1999
DOI: 10.1046/j.1365-2044.1999.01072.x
|View full text |Cite|
|
Sign up to set email alerts
|

THIS ARTICLE HAS BEEN RETRACTED: Relationship between stimulating current and accelographic train‐of‐four response at the great toe

Abstract: SummaryThe incidence and origin of contamination of the vocal cords in 53 trauma patients was studied when tracheal intubation was performed before hospital admission. Eighteen patients (34%) had gross contamination which was blood in 15 patients and gastric contents in three patients. This has implications for prehospital airway management and particularly for use of the laryngeal mask airway. Since victims of major trauma may have full stomachs and impaired airway reflexes they are assumed to be at high risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It has been reported that the value of T1 recorded at the supramaximal current is generally > 90% of the T1 value elicited at 60 mA. [2][3][4] Thus, the lowest current able to produce a value of T1 of more than 90% of the value of T1 recorded at 60 mA was regarded as the supramaximal current. This method of determining the supramaximal current is in accordance with previous reports.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the value of T1 recorded at the supramaximal current is generally > 90% of the T1 value elicited at 60 mA. [2][3][4] Thus, the lowest current able to produce a value of T1 of more than 90% of the value of T1 recorded at 60 mA was regarded as the supramaximal current. This method of determining the supramaximal current is in accordance with previous reports.…”
mentioning
confidence: 99%
“…This method of determining the supramaximal current is in accordance with previous reports. [2][3][4] Once the supramaximal current had been determined in each patient in the four groups, the TOF stimuli were delivered every 20 sec at the supramaximal current for approximately five minutes until the accelerographic and mechanical responses stabilized. Thereafter, the accelerographic value of T1 and the mechanical twitch height in response to T1 were regarded as controls.…”
mentioning
confidence: 99%
“…As the skin thickness increases, the supramaximal stimulating current for the monitoring of neuromuscular blockade becomes high 26 ). It was noted that skin thickness was greater in men than in women27).…”
Section: Resultsmentioning
confidence: 99%